2020
DOI: 10.1002/jbmr.4401
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Jmjd3/p16Ink4a Signaling Pathway Causes Bizarre Parosteal Osteochondromatous Proliferation (BPOP)-like Lesion in Mice

Abstract: Bizarre parosteal osteochondromatous proliferation (BPOP), or Nora's lesion, is a rare benign osteochondromatous lesion. At present, the molecular etiology of BPOP remains unclear. JMJD3(KDM6B) is an H3K27me3 demethylase and counteracts polycomb‐mediated transcription repression. Previously, Jmjd3 was shown to be critical for bone development and osteoarthritis. Here, we report that conditional deletion of Jmjd3 in chondrogenic cells unexpectedly resulted in BPOP‐like lesion in mice. Biochemical investigations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(87 reference statements)
0
1
0
Order By: Relevance
“… 27 In addition, an animal experiment indicated that the Jmjd3/p16 Ink4a signaling pathway might play an important role in the development of BPOP. 28 Although the above studies suggest some therapeutic targets for BPOP, no specific drug is applied in the clinical setting. Because BPOP is a slowly growing benign lesion, conservative treatment is suggested when patients have no symptoms.…”
Section: Discussionmentioning
confidence: 99%
“… 27 In addition, an animal experiment indicated that the Jmjd3/p16 Ink4a signaling pathway might play an important role in the development of BPOP. 28 Although the above studies suggest some therapeutic targets for BPOP, no specific drug is applied in the clinical setting. Because BPOP is a slowly growing benign lesion, conservative treatment is suggested when patients have no symptoms.…”
Section: Discussionmentioning
confidence: 99%